Moderasi Asas Kemandirian Tamansiswa pada Akuntabilitas Dana Desa di Desa Kapanewon Tempel Kabupaten Sleman, Daerah Istimewa Yogyakarta - Ayem, Sri; Tunga, Karolina (Mahesa Research Center, 2024)
This research was conducted to examine the influence of the competence of village government officials and internal control systems on accountability in village funds management with the principle of independence as a moderating variable in Kapanewon Tempel Villages, Sleman Regency. The method used in this research is descriptive quantitative and primary data is taken through questionnaires. This research is a quantitative research type. The population in this study were village officials in the villages in Kapanewon Tempel. Units of analysis are the village head, BPD, village secretary, village treasurer, head of finance, head of planning, head of administration, and head of services. Samples were taken using a purposive sampling technique, which makes the entire population sampled in this research. The total sample in this research was 64 respondents. Data analysis shows that 1) the competence of village officials has a positive influence on the accountability of village fund management; 2) the internal control system has a positive influence on the accountability of village fund management; 3) the principle of independence does not moderate the competence of village officials towards accountability in managing village funds, and 4) the principle of independence does not moderate the internal control system towards accountability in managing village funds.